Gauging Algerian EFL Teachers’ Awareness of the 21st Century Compulsory Skills: Case of EFL Teachers at IbnKhaldoun University of Tiaret - Mehdaoui, Ahmed; Benabed, Ammar (Technium Social Sciences Journal, 2022)
The development of 21st century skills is now widely accepted as a vital competency for graduates to succeed in today's world-society and economy. Employers, students, and teachers' perceptions of the skill gaps have been the focus of some research looking at the relationship between 21st century abilities and student knowledge. There are not many researches on how teachers' awareness affects their students' acquisition of 21st century abilities. The question that arises from this study is if the EFL teachers in Algeria are aware of the 21st-century learning needs that are necessary to implement any educational program. The purpose of this study is therefore to examine the extent of Algerian EFL university professors' awareness of 21st-century abilities. The degree to which they are open to change can be ascertained by looking at their level of self-awareness. At the same time, it will shed light on the apparent disparity in educational attainment between English majors and their peers. There were 13 English language teachers from IbnKhaldoun University of Tiaret who volunteered to be part of the study in order to gather data, and both quantitative and qualitative data were collected using a questionnaire. There was a correlation between teachers' knowledge of 21st century skills and their readiness to use them in their classrooms, according to the findings. In order to fully integrate 21st century skills into the classroom, teachers must overcome certain significant pedagogical issues such as excessive class size, a lack of teacher training, and an absence of accompanying instruments and technology equipment. Researchers drew conclusions and recommendations based on their findings.